Transfer ke Daerah: Dana Otonomi Khusus Papua, Perspektif Institusional Isomorphism - Ariyadi, Yuli; Hadi Kusuma, I Putu Danny (Jurnal Manajemen Perbendaharaan, 2024)
This research aims to understand the dynamics of the implementation of Papua's Special Autonomy, including the significant events that serve as the basis for the application and management of Papua’s Special Autonomy funds seen from the perspective of institutional isomorphism. This qualitative study uses a case study method, approached through phenomenological interpretation and an interpretative worldview perspective. Data collection was conducted from August 6, 2023, to August 25, 2023, through literature reviews and interviews with informants. The research findings indicate that Coercive Isomorphism, Mimetic Isomorphism, and Normative Isomorphism occur in various forms and periods. However, not all dimensions of institutional isomorphism are present in every period. The central government plays a more dominant role in regulating and managing Papua's Special Autonomy funds. In the future, the central government could allocate a greater portion, role and authority to the regional government to regulate and manage Papua's Special Autonomy funds to give benefits and improve the welfare of the Papuan People.